2018
DOI: 10.1177/1748048518775000
|View full text |Cite
|
Sign up to set email alerts
|

Framing social conflicts in news coverage and social media: A multicountry comparative study

Abstract: This study attempts to understand how geopolitical proximity influences framing of social conflicts in news coverage and social media discussions. Within the context of 2013 Little India riot in Singapore, a manual content and automated linguistic analyses are conducted on 227 news articles and 4,495 tweets. A multinational comparison suggests that news media follow the traditional hypothesis of geopolitical proximity and international news coverage. However, Twitter seems less constrained by geopolitical boun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…These political frames work as communication tools that identify, evaluate, and prescribe the concerns to make sense of only what we watch or read. Additionally, although the issues are related to a certain region or country, geopolitical proximity is another major component that makes social media, particularly Twitter, a distinguished political communication and framing (Ahmed et al, 2019). Hence, we also found self-representation frames widely used by the Bahraini female candidates to represent themselves on Twitter.…”
Section: Discussionmentioning
confidence: 68%
“…These political frames work as communication tools that identify, evaluate, and prescribe the concerns to make sense of only what we watch or read. Additionally, although the issues are related to a certain region or country, geopolitical proximity is another major component that makes social media, particularly Twitter, a distinguished political communication and framing (Ahmed et al, 2019). Hence, we also found self-representation frames widely used by the Bahraini female candidates to represent themselves on Twitter.…”
Section: Discussionmentioning
confidence: 68%
“…While the mainstream press created dialogic moments for frames on structural remediation to emerge, unlike in previous studies (e.g., Tan, 2016;Goh et al, 2017;Ahmed et al, 2019;Kaur-Gill et al, 2019), the press also continued to center sensationalist articles that evoked streams of xenophobia. The various opposing dialectics play out in mainstream reporting.…”
Section: Margins and Voicementioning
confidence: 71%
“…However, it is noteworthy to mention that with competing voices came competing threads on the discussion of migrant workers and their health. Thus, while state voice remained central in narratives on the Little India Riot episode (Kaur et al, 2016), with Ahmed et al (2019) citing that the mainstream press reported the riot without diving into the cause and reasons behind the conflict, attributing this to the stringent press control that promotes the state's position.…”
Section: Margins and Voicementioning
confidence: 99%
“…The methodological flexibility shown by framing studies is also significant when analysing all kinds of issues: from specific subjects such as electoral campaigns or the image of a leader (Sahly et al 2019;Louie and Viladrich 2021) to long-term problems such as climate change, social protest, the refugee crisis, or cases of sexual harassment (Lück et al 2018;Ahmed et al 2019;Starkey et al 2019), from very different techniques and designs. In general, framing studies are characterised by proposing a great diversity of models of content analysis of the informative or political message (Matthes and Kohring 2008), while surveys and experimental designs have had less application up to a few years (Brugman and Burgers 2018;Banks et al 2021).…”
Section: Reasons For a Research Successmentioning
confidence: 99%